2015
DOI: 10.1021/acs.jpcb.5b06594
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Carboxylate/Water Networks on the Surface of the PsbO Subunit of Photosystem II

Abstract: Clusters of charged groups on the surface of proton-transfer proteins may participate in proton transfers. PsbO, an extrinsic subunit of photosystem II, is a carboxylate-rich protein part of an extensive hydrogen-bond network leading to the catalytic site. This raises the important question as to whether specific clusters of carboxylate groups on the surface of PsbO may directly assist transfer of protons from the catalytic site to the bulk. From molecular dynamics simulations of PsbO in aqueous solution, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 82 publications
3
67
0
Order By: Relevance
“…Proton transfer in the protein PsbO, a subunit of photosystem II (PSII), involves low-mobility water molecules close to the surface that form part of an extended water-carboxylate network (61). Some of these waters might also assist the docking of PsbO into the PSII complex.…”
Section: How Hydration Water Assists Protein Functionmentioning
confidence: 99%
“…Proton transfer in the protein PsbO, a subunit of photosystem II (PSII), involves low-mobility water molecules close to the surface that form part of an extended water-carboxylate network (61). Some of these waters might also assist the docking of PsbO into the PSII complex.…”
Section: How Hydration Water Assists Protein Functionmentioning
confidence: 99%
“…PsbO appears to regulate functioning of PSII. Indeed, removal of PsbO from PSII leads to partial loss of the manganese ions from the catalytic center, decreased oxygen production, and perturbed dynamics of water at the active site and of the reaction cycle [58]. PsbO2 is the minor isoform in the wild-type.…”
Section: Resultsmentioning
confidence: 99%
“…X‐ray crystallography and computation suggested an extended proton network around the OEC, serving as starting point for proton transport pathways towards the thylakoid lumen. PsbO interacts with subunits D1 and D2 of PSII through the loops Asp158–Lys188 and Asp222–Ala228, and their residues Asp158, Asp222–Asp224, His228, and Glu229 are part of a putative proton exit pathway . The smallest distance between PsbO and the OEC is 17 Å, as measured in a PSII crystal structure (PDB ID: 3WU2).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the evolutionarily conserved extrinsic PSII subunit PsbO, which is located at the luminal side of PSII (Figure A), might provide a small buffering capacity or pathways for proton removal, or might act as a proton antenna, in addition to its established function in controlling the chloride and calcium concentrations at the OEC, thereby (and possibly also by other means) stabilizing the manganese complex . A pH buffer functionality of the PsbO carboxylate groups could transiently avoid acidification of the thylakoid lumen, for conditions of fluctuating light intensities (but not under continuous illumination), that easily and often occur in a natural habitat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation